O envolvimento do discente universitário com o trabalho de conclusão de curso: o caso da turma de Educação do campo - 2015, UFPA - RIBEIRO, Mayara Helenice Brito (2019)
The aim of this paper is to investigate the involvement of students of the field education course with the work of graduation through a case study in the 2015 class with emphasis on natural sciences, from the Federal University of Pará campus of Abaetetuba, with the intention to contribute to the improvement of the quality of the TCC. The research had the participatory qualitative approach, the explanatory descriptive type, it has as a delineation the case study composed of primary and secondary data, which were obtained through semi-structured interviews and focal group, having as participants of the research the students of the referred class, part of course coordination, and faculty faculty teachers. Data were organized based on content analysis. The study made possible to understand about the theme The involvement of the university student with the work of conclusion of the course: the case of the field education class 2015, UFPA. It revealed that the political project of the course is far from the demands that the course currently has, that among the curriculum components of the course there are no specific subjects that deal with the elaboration of the CBT, and few subjects related to the emphasis of the course. Given the results obtained, it was identified that the involvement of students in the 2015 Education class is complex due to the lack of disciplines, both for the elaboration of the CBT and for subjects related to emphasis. Thus, it is necessary to reflect on the redesign of the PPP of the course, so that it meets the demands that the course currently has.